Chemiosmotic systems in bioenergetics: H+-cycles and Na+-cycles. Issue 6 (December 1991) - Skulachev, Vladimir P.
Abstract : The development of membrane bioenergetic studies during the last 25 years has clearly demonstrated the validity of the Mitchellian chemiosmotic H + cycle concept. The circulation of H + ions was shown to couple respiration-dependent or light-dependent energy-releasing reactions to ATP formation and performance of other types of membrane-linked work in mitochondria, chloroplasts, some bacteria, tonoplasts, secretory granules and plant and fungal outer cell membranes. A concrete version of the direct chemiosmotic mechanism, in which H + potential formation is a simple consequence of the chemistry of the energy-releasing reaction, is already proved for the photosynthetic reaction centre complexes. Recent progress in the studies on chemiosmotic systems has made it possible to extend the coupling-ion principle to an ion other than H + . It was found that, in ceertain bacteria, as well as in the outer membrane of the animal cell, Na + effectively substitutes for H + as the coupling ion (the chemiosmotic Na + cycle). A precedent is set when the Na + cycle appears to be the only mechanism of energy production in the bacterial cell. In the more typical case, however, the H + and Na + cycles coexist in one and the same membrane (bacteria) or in two diffeerent membranes of one and the same cell (animals). The sets of Δμ̄H + and Δμ̄Na + generators as well as Δμ̄H + and Δμ̄Na + consumers found in different types of biomembranes, are listed and discussed.